Cardiac myocyte-specific transgenic ecSOD targets mitochondria to protect against Ca2+ induced permeability transition - Luo, Jianzhu; Obal, Detlef; Dimova, Neviana; Tang, Xian-Liang; Rokosh, Gregg (Frontiers in Physiology, 2013)
ecSOD function has prototypically been associated with the extracellular space due to its secretion and localization to the extracellular matrix. A myocyte-specific ecSOD transgenic mouse has shown that it can also be localized to the myocyte intracellular compartment and is capable of attenuating Reactive oxygen species (ROS) formation and increasing NO bioavailability after ischemia reperfusion. Here, the subcellular localization of transgenic ecSOD was further defined by subcellular fractionation, immunofluorescent confocal microscopy, and Western analysis. Its impact on mitochondrial function was assessed by mitochondrial permeability transition (MPT). ecSOD was found to exist in cytosolic and nuclear fractions in addition to membrane. Colocalization of ecSOD with myocardial mitochondria was further demonstrated by confocal microscopy and subcellular fractionation of mitochondria and Western analysis. Isolated ventricular myocytes from cardiac-specific transgenic ecSOD mice were protected from hypoxia reoxygenation injury. Increased ecSOD colocalization to myocardial mitochondria in ecSOD Tg hearts limited MPT in response to Ca2+ challenge. These results demonstrate that ecSOD is not restricted to the extracellular space and can alter MPT response to Ca2+ suggesting mitochondrial localization of ecSOD can affect key mitochondrial functions such as MPT which are integral to cell survival.